OPEN PUBLIC DATA: HOW WE USE IT AND HOW IT USES US - Hyland-Wood, Bernadette (AoIR Selected Papers of Internet Research, 2023)
Data policy aims to understand how governments, industry, academia, and civil society understand data availability and use. Data policy studies are broad in scope and include theory and practice of open sources of data from traditional sources (e.g., statistics and public health government agencies); representation and interpretation of data; investigations of the social relations and impacts of open public data; and attitudes surrounding data stewardship and public data availability and use. This study’s empirical research is based on two case studies of the Australian and New Zealand Open Data programs between 2010 and 2020. Based on current scholarship, some factors affecting open data supply were confirmed, and new insights were generated. Social psychology theorising concerning identity leadership was confirmed. When leaders promoted a sense of ‘us’ and ‘who we are’, data stewards were more likely to advance a shared vision for making data available for reuse. The concepts of _collateral peers_ and _collateral peer networks_ were introduced to data policy scholarship. Collateral peer networks engage in multistakeholder governance with no apparent leader-follower relationship. Instead, peers (in function but not necessary title) collaborate across the public service, at various levels of government, and with experts in research institutions (e.g., publicly funded scientific and applied research organisations). Future areas for public interest technology, specifically data policy research, include how researchers and practitioners can prioritise data stewardship, open data communities, and multistakeholder governance, especially during prolonged and compounding crises.